2020
DOI: 10.1177/2399808320947729
|View full text |Cite
|
Sign up to set email alerts
|

A computer-assisted expert algorithm for real estate valuation in Spanish cities

Abstract: Some of the most overlooked valuation systems in current literature are those based on expert algorithms. Yet these algorithms can form the basis of a good estimation of the value of real estate since they allow simple computational methods that use big data to be integrated with the appraiser’ own knowledge of the situation. The main usefulness of the methodology is an ongoing mortgage risk appraisal for banking institutions. The current expert algorithms based on the sales comparison approach use the arithme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Kim et al (2020) used an automated sales comparison method to evaluate apartments in Korea, and found that their approach outperformed machine learning methods. Using a computer-assisted expert algorithm, Larraz et al (2021) consider differences in characteristics compared to similar properties and their relative location.…”
Section: The Market Comparison Approachmentioning
confidence: 99%
“…Kim et al (2020) used an automated sales comparison method to evaluate apartments in Korea, and found that their approach outperformed machine learning methods. Using a computer-assisted expert algorithm, Larraz et al (2021) consider differences in characteristics compared to similar properties and their relative location.…”
Section: The Market Comparison Approachmentioning
confidence: 99%
“…Larraz et al. ( 2021 ) use a computer-assisted expert algorithm and consider differences in characteristics compared to similar properties and their relative location.…”
Section: Literature Reviewmentioning
confidence: 99%